2005
DOI: 10.4049/jimmunol.174.5.2591
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cell Immunity Against a Tumor/Self-Antigen Is Augmented by CD4+ T Helper Cells and Hindered by Naturally Occurring T Regulatory Cells

Abstract: CD4+ T cells control the effector function, memory, and maintenance of CD8+ T cells. Paradoxically, we found that absence of CD4+ T cells enhanced adoptive immunotherapy of cancer when using CD8+ T cells directed against a persisting tumor/self-Ag. However, adoptive transfer of CD4+CD25− Th cells (Th cells) with tumor/self-reactive CD8+ T cells and vaccination into CD4+ T cell-deficient hosts induced autoimmunity and regression of established melanoma. Transfer of CD4+ T cells that contained a mixture of Th an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
510
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 664 publications
(539 citation statements)
references
References 66 publications
18
510
2
1
Order By: Relevance
“…In addition to their role in autoimmunity, T reg participate in transplantation tolerance and tumour immunity. Although the mechanisms of suppression by T reg remain to be determined in vivo, many investigators have reported that T reg can inhibit immune responses mediated by CD4 þ CD25 À T cells and CD8 þ T cells in vitro via cell -cell contact (Sakaguchi et al, 1995;Sakaguchi, 2000;Shevach, 2002;Camara et al, 2003;Anatomy et al, 2005). T reg express CD25 (interleukin-2 receptor a), glucocorticoid-induced tumour necrosis factor receptor, and cytolytic T lymphocyte-associated antigen 4 on their surface.…”
mentioning
confidence: 99%
“…In addition to their role in autoimmunity, T reg participate in transplantation tolerance and tumour immunity. Although the mechanisms of suppression by T reg remain to be determined in vivo, many investigators have reported that T reg can inhibit immune responses mediated by CD4 þ CD25 À T cells and CD8 þ T cells in vitro via cell -cell contact (Sakaguchi et al, 1995;Sakaguchi, 2000;Shevach, 2002;Camara et al, 2003;Anatomy et al, 2005). T reg express CD25 (interleukin-2 receptor a), glucocorticoid-induced tumour necrosis factor receptor, and cytolytic T lymphocyte-associated antigen 4 on their surface.…”
mentioning
confidence: 99%
“…Cytotoxic activity of the CTLs was maintained and mice were protected from tumour growth (Marzo et al, 2000). Persistent CD4 þ help and IL-2 secretion are required to maintain CD8 cell function and numbers (Antony et al, 2005). Direct cell-cell contact from CD4 cells can also protect effector CD8 cells from activationinduced cell death (Kennedy and Celis, 2006).…”
Section: Antigen Presenting Cells: the Gateway To Immunity Or Toleranmentioning
confidence: 99%
“…This notion, as it relates to contemporary definitions of regulatory T cells (T regs ), has not been extensively explored. However, one recent study implicated T reg depletion in the enhanced efficacy of adoptive T-cell immunotherapy for transplanted melanomas following whole-body irradiation in a murine model (Antony et al, 2005). Enhanced functionality of adoptively transferred T cells following radiation induced lympho-depletion has also been linked to increased availability of homeostatic cytokines .…”
Section: Enhancement Of Antitumor Effector Mechanismsmentioning
confidence: 99%